Analysis of the diagnostic value of peripheral blood immune inflammatory indicators of female bladder pain syndrome - Wang, Yinglei; Liu, Shenglai; Shi, Haonan; Xie, Chunxiao; Li, Peng; Jia, Kaipeng; Tang, Yang; Hu, Hailong (Frontiers in Surgery, 2025)
Introduction and hypothesisFemale bladder pain syndrome (FBPS), previously known as interstitial cystitis/bladder pain syndrome (IC/BPS). Numerous research indirectly prove that Female bladder pain syndrome (FBPS) is associated with immune-related inflammation. According to the correlation analysis between peripheral blood immune-inflammatory markers and disease diagnosis, this research further verifies the potential diagnostic value of peripheral blood inflammatory markers in FBPS.MethodA total of 149 women with bladder pain syndrome who visited the urology department of our hospital from January 2013 to December 2024 and 149 healthy controls Patients who underwent health examinations at the physical examination center of our hospital from January 2022 to January 2023 were screened. All patients' peripheral blood inflammatory markers at admission included Neutrophil-to-Lymphocyte ratio (NLR), Systemic Immune Inflammation index (SII), et al. The maximum bladder capacity (MBC) during surgery served as the bladder volume. Multivariate binary regression was used to calculate the correlation between these indicators and disease diagnosis as well as MBC. The correlation between these indicators and MBC is secondary outcomes. The optimal cut-off value for the parameters was identified using the receiver operating characteristic (ROC) curve and its area under the curve (AUC) over time.ResultsCompared with the control group, patients in the observation group demonstrated significantly higher SII, NLR, PLR, neutrophil count, whereas peripheral blood platelet count (PLT) and absolute lymphocyte count decreased, with statistically significant differences (all P < 0.05). Multivariate binary logistic regression analysis revealed increased NLR as an independent risk factor for FBPS. Compared with the normal bladder capacity group, patients with small bladder capacity demonstrated significantly lower SII, PLR, PLT, with statistically significant differences (all P < 0.05). Multivariate binary logistic regression analysis revealed decreased PLT as an independent risk factor for reduced bladder capacity.ConclusionPeripheral blood inflammation indicators can be employed as an auxiliary diagnostic standard for FPBS, and NLR can be used as an independent diagnostic indicator for FBPS. However, further prospective studies are warranted to identify the causal relationship of these indicators with patient symptoms.